Moral and Religious Values in the Novel "Negeri Lima Menara" by A. Fuadi and its Relationship as Reading Materials in Schools Year 2020/2021 - Putri Apriani; Erikson Saragih; Rosliani (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
This study aims to describe the moral values and religious values in the novel Negeri Lima Menara in the development of learning, as well as to describe the relevance of moral and religious values in Negeri Lima Menara as student reading material. The method used in this research is qualitative descriptive analytical method, which is to provide an understanding of the elements that are the center of the research so as to achieve the expected results in the Negeri Lima Menara Novel by A. Fuadi. The results showed that moral values consisted of 6 categories, namely honesty with a frequency of 13 or 21.311%, authentic values (confidence) with a frequency of 15 or 24.590%, willingness to be responsible with a frequency of 14 or 22.950%, moral independence with a frequency of 7 or 11,475%, moral courage with a frequency of 8 or 13,114% and humility with a frequency of 4 or 9,677%. Meanwhile, the religious values in the Negeri Lima Menara novel by A. Fuadi consist of 6 categories, namely submission and obedience with a frequency of 7 or 24.137%, a life full of deference with a frequency of 7 or 24.137%, inner feelings related to God with a frequency of 5 or 17,241%, feelings of sin with a frequency of 5 or 17,241%, feelings of fear with a frequency of 2 or 6,896% and acknowledging the greatness of God with a frequency of 5 or 17,241%.